(untitled) (Eurasian Research Bulletin, 2024)
The article discusses the working processes of irrigation machines and other important structures, such as the lighting system, energy supply, and other issues observed. Additionally, the article analyzes the principles of operation of irrigation machines, their practical application, and the significance of their use. The annotation supports other research on this topic and provides information on the technological development of irrigation machines and the benefits gained from their use.